The individuality of metrical engagement: describing the individual differences of movements in response to musical meter - Martínez, Isabel Cecilia (2015)
Evidence behind theories about musical meter and rhythm is based on averages across empirical sets of data. Theory is also commonly forged from general observations of music practices. Ethnomusicology describes rhythm and dance based on patterning characterizations inside cultures. Without neglecting the value of that knowledge, so far we know very little about how individuals´ bodies respond to music. Derivation of common laws from controlled experimentation may have obfuscated the understanding of differences between individuals, their music, movements and dance. How large are these differences as expressed, and how our bodies map these idiosyncrasies are questions that still need answers. In this paper we look into a detailed account of differences between individuals by looking at their free movement responses to music. Using the state-of-the-art of motion capture technologies and a set of analytical techniques we uncover the embodied metric organization, exposing the idiosyncrasies between different people.